2021
DOI: 10.3390/genes12111839
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with Tumor Development in Individuals Diagnosed with Beckwith–Wiedemann Spectrum: Novel Tumor-(epi)Genotype-Phenotype Associations in the BWSp Population

Abstract: Beckwith–Wiedemann Spectrum (BWSp) is the most common epigenetic childhood cancer predisposition disorder. BWSp is caused by (epi)genetic changes affecting the BWS critical region on chromosome 11p15. Clinically, BWSp represents complex molecular and phenotypic heterogeneity resulting in a range of presentations from Classic BWS to milder features. The previously reported tumor risk based on Classic BWS cohorts is 8–10% and routine tumor screening has been recommended. This work investigated the tumor risk and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…[16] They should be referred to a clinical geneticist, and an examination and molecular testing including 11p15.5 analysis in deoxyribonucleic acid (DNA) should be performed. [17][18][19] Baseline abdominal ultrasonography is advised to assess the presence of organomegaly. For significant ILO, the advice is to establish the underlying (epi)genetic cause and initiate surveillance while awaiting the test results.…”
Section: Discussionmentioning
confidence: 99%
“…[16] They should be referred to a clinical geneticist, and an examination and molecular testing including 11p15.5 analysis in deoxyribonucleic acid (DNA) should be performed. [17][18][19] Baseline abdominal ultrasonography is advised to assess the presence of organomegaly. For significant ILO, the advice is to establish the underlying (epi)genetic cause and initiate surveillance while awaiting the test results.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these studies, two of 55 patients (3.4%) in our ILO group also developed tumors; molecular testing was negative in two ILO patients with embryonal tumors, while three of four patients with atypical and classic phenotypes had pUPD11 and an IC1-GOM. Among the molecular subgroups of BWSp patients, the risk of tumor development was highest in patients with IC1-GOM (28%), 2.5% in IC2-LOM, and 16% in pUPD11 [ 2 , 12 , 26 ]; 152 patients with LO were evaluated for tumor frequency; in 34 patients who developed tumors, epigenetic alterations were detected in 61.8% pUPD11, 32% IC1-GOM, and 5.9% IC2-LOM [ 14 ]. Another study reported that the molecular subgroup with the highest tumor incidence was pUPD in LO patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that embryonal tumor risk is higher in BWSp patients, especially in LO, has increased the importance of both clinical diagnosis and the detection of methylation alterations in the 11p15.5 region in this group of patients [ 12 , 13 , 14 ]. On the other hand, Wilms tumor (WT) and other embryonal cancers associated with BWSp may be the first recognized manifestation of the syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Mosaicism in the context of BWSp is well‐established and presents the primary challenge to obtaining the accurate molecular diagnosis within this population (Brioude et al, 2018; Brzezinski et al, 2017; Duffy, Getz, et al, 2021). While classically associated with pUPD11 or IC1‐GOM, the notion of mosaicism within the context of IC2‐LOM profiles established in blood was previously proposed (Brzezinski et al, 2017), although met with considerable criticism (Brioude et al, 2018).…”
Section: Potential Etiologies Of Clinical Variability With a Single F...mentioning
confidence: 99%